Assessment of autoflush machine for cleaning of toilet area/elimination area in weaner pen - SINGH, ANUP KUMAR; PATEL, B H M; SINGH, MUKESH; GAUR, G K; VERMA, M R; DUTT, TRIVENI; CAROLINA, P (The Indian Journal of Animal Sciences, 2018)
An attempt was made to develop auto-flush machine for cleaning of toilet area/elimination area. To study the auto-flush system, a total of 10 weaners were divided into two groups (having 5 each), viz. G1 (weaners kept in a modified intensive pen with auto flush system) and G2 (weaners in intensive pen without auto-flush). The defecation pattern/trend was observed 24 h consecutively for 5 days. Each weaner defecated 8.40±0.23 and 8.92±0.13 times per day in G1 and G2 respectively. The auto-flush was assessed indirectly based on parameters like hygiene score of floor, hygiene score of animals, amount of water consumed and manpower required for cleaning of pen in 5 days. Hygiene score of floor was higher in G1 (143±0.63) compare to G2 (112.2±1.7). Hygiene score of animals was higher in G1 (5) compared to G2 (2.6). Water consumed for cleaning was lower in G1 (162.8±9.06 litres) than G2 (212±1.4 liters). Manpower requirement in G1 (7.85±0.24 sec) was lower than G2 (175.48±2.11 sec). It can be concluded that all weaners used the elimination area for defecation in G1. The auto-flush system helped in saving water, labour time and maintained the cleanliness of both floor and animal.